2020
DOI: 10.1186/s12890-020-01351-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles of subclinical disease among pulmonary tuberculosis patients: a prospective cohort study in South Korea

Abstract: Background Subclinical tuberculosis (TB) is a potential target for public health intervention because its early identification may reduce TB transmission. We aimed to describe the clinical and laboratory findings of subclinical disease among pulmonary TB patients and compared treatment outcomes for subclinical and active diseases. Methods In this prospective cohort study, we enrolled adult patients aged ≥ 19 years with pulmonary TB between 2016 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
1
12
0
Order By: Relevance
“… 38 This could mean that we may be systematically underestimating the contribution of subclinical cases, 37 the vast majority of which are smear-negative. 39 Mechanistically, if you consider the significant aerosol production arising from routine activities like speaking or singing, cough would not be required for transmission. 40 While we believe our findings are an accurate reflection of transmission ascertainment reliant on routine contact tracing practice and while we attempt to account for unidentified secondary cases, the evolving literature around the role of transmission from subclinical cases shows the challenge in attributing precise transmission rates based on smear-status.…”
Section: Discussionmentioning
confidence: 99%
“… 38 This could mean that we may be systematically underestimating the contribution of subclinical cases, 37 the vast majority of which are smear-negative. 39 Mechanistically, if you consider the significant aerosol production arising from routine activities like speaking or singing, cough would not be required for transmission. 40 While we believe our findings are an accurate reflection of transmission ascertainment reliant on routine contact tracing practice and while we attempt to account for unidentified secondary cases, the evolving literature around the role of transmission from subclinical cases shows the challenge in attributing precise transmission rates based on smear-status.…”
Section: Discussionmentioning
confidence: 99%
“…In case of HIV infection—the most important risk factor in developing active TB ( 22 )—as soon as antiretroviral therapy is administered, the mortality rate decreases and the prognosis is improved ( 3 , 21 , 23 ). This particular need of early bacterial identification is increased by low-adherence antituberculotic regimens: first-line agents represented by isoniazid, rifampicin, pyrazinamide, ethambutol, and streptomycin (mostly used in primary active TB), and second-line agents (mostly used in resistant bacilli strains) ( 5 , 24 – 26 ). First-line regimens are recommended as a directly observed therapy (DOT) in drug-susceptible TB in individuals residing in settings with a low proportion of resistant strains for 6 months as follows: intensive phase (rapid mycobacterial reduction) when agents are administered daily for 2 months and continuation phase (sterilization phase with isoniazid and rifampicin given thrice every week) for the next 4 months ( 21 , 24 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among studies that compared the screening and diagnostic test outcomes between people with subclinical TB and clinical TB disease ( table 2 ), those with clinical disease were more likely to test positive on NAAT or culture. Five studies reported a higher proportion of positive radiologic tests among those with clinical TB disease, of which two were statistically significantly different [ 18 , 23 , 37 , 41 , 76 ]. However, this review also identified two studies that described a higher proportion of chest radiographs suggestive of TB disease among people with subclinical TB relative to those with clinical disease [ 19 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific chest radiography findings included a higher proportion of multilobar infiltrates among those with clinical TB disease [ 23 , 76 ]. Two studies that examined the radiographic findings of chest computed tomography (CT) found higher proportions of multi-lobar involvement [ 37 , 41 ], consolidation [ 37 ], and fibrotic scar [ 37 ] among those with the clinical disease compared to subclinical TB. The presence of cavitary lesions was significantly associated with clinical TB disease [ 76 ].…”
Section: Resultsmentioning
confidence: 99%